Errore di raccomandazione. DensitÃ del testo e ampliamento del senso: percorsi di visione allâepoca degli algoritmi - Martina Federico (Ocula)
The essay is intended to be a sociosemiotic reasoning on the potential cultural irradiations that are triggered from a phenomenon of internal défaillance in the recommendation systems used by film streaming platforms. At first, the functioning of the recommendation algorithms underlying the streaming platforms is presented, intersected with a discourse on gender attribution (tagging); it proceeds accordingly with some reflections that take their cue from an error, or rather a case of poorly calibrated "balancing" of gender in the tagging operation of the film Palombella rossa (Nanni Moretti, 1989) which is presented as a sports-themed film; and taking a cue from this, finally, an opportunity is given to rethink the intersection between recommendation procedures and genre attribution, proposing some ideas about the logics that guide the vision pathways in the age of algorithms.